2007
DOI: 10.1002/jrs.1832
|View full text |Cite
|
Sign up to set email alerts
|

The role of dangling bonds in the electronic and vibrational properties of hydrogenated amorphous silicon nitrides (a‐SixNx : H)

Abstract: Hydrogenated amorphous silicon nitrides have been obtained as thin films deposited by plasma-enhanced chemical vapour deposition onto (100) silicon wafers. Two different samples have been obtained with similar deposition conditions in the plasma chamber but varying the SiH 4 /NH 3 molar ratio. We used various spectroscopic techniques to ascertain how the different sample composition influences the remarkable spectroscopic differences observed. The contribution of the Si dangling bonds, randomly dispersed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Another possibility can be the formation of dangling bonds in some vacancies, as already noted for materials with Al V coordinated or for hydrogenated silicon for instance in Ref. 63. It has been realised in the case of a-Si compound that the presence of hydrogen can strongly affect the creation and annihilation of dangling bonds [64,65] .…”
Section: Broad 1000-4000 CM −1 Raman Featurementioning
confidence: 98%
“…Another possibility can be the formation of dangling bonds in some vacancies, as already noted for materials with Al V coordinated or for hydrogenated silicon for instance in Ref. 63. It has been realised in the case of a-Si compound that the presence of hydrogen can strongly affect the creation and annihilation of dangling bonds [64,65] .…”
Section: Broad 1000-4000 CM −1 Raman Featurementioning
confidence: 98%
“…Furthermore, it has been reported that nitrogen doping can change the structural characteristics of the undoped Si : H thin films through the interaction with the hydrogen bonds of the films. [7] However, the use of Raman spectroscopy to study the influence of nitrogen doping on the structural evolution in P-doped n-type a-Si : H thin films is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the role of dangling bonds in the electronic and vibrational properties of hydrogenated amorphous silicon nitrides (a-Si 1−x N x :H) was studied by Cataliotti and Compagnini. [178] Liquids and Liquid Interactions…”
Section: Glasses Ceramics and Disordered Materialsmentioning
confidence: 99%